(untitled) (American Journal of Energy and Natural Resources, 2023)
Levels of heavy metals in mining areas differ from region to region depending on the level of operations and activities engaged at the mining site. The study assessed the extent of heavy metals contamination in the available water and sediments in mining endowed enclaves in Ghana. A total of forty-eight (48) samples, 24 each of water and sediments samples were taken. At each mining site, 4 samples each of water and sediments samples were taken and studied. Water and sediment samples were taken to the laboratory to determine level of mercury and arsenic. For the sediments, the average levels of Hg ranged from 0.057-0.145ppm and that of As levels in the soil sediments ranged from 0.084-0.087ppm. The average levels of Hg in water samples ranged from 0.010-0.086ppm and that of As levels in the water samples ranged from 0.004-0.008ppm. There were significance differences (p<0.05) in the levels of Hg and As of the various mining sites for the water and the sediments. All the samples (water and sediments) taken from the various mining sites had Hg above the recommended levels whereas As for samples were below the recommended levels. There should be enforcement of more stringent water and land monitoring and pollution scheme through Environmental Protection Agency (EPA) and the Minerals Commission.